THE FREQUENCY OF ALLELIC VARIANTS OF GENES TNFRI AT POSITIONS -609 AND -1207 AND TNFRII AT POSITIONS -1709 AND -3609 IN HEALTHY DONORS AND PATIENTS WITH RHEUMATOID ARTHRITIS - N. S. Shkaruba; P. P. Vasiliev; A. N. Silkov; J. A. Sennikova; J. A. Lopatnikova; A. E. Sizikov; T. A. Kalashnikova; L. P. Sizyakina; J. B. Shulman; S. V. Dolgikh; V. I. Mazurov; S. V. Sennikov (Acta Biomedica Scientifica, 2012)
In this paper we studied the frequency of allelic variants of genes TNFRI at positions -609 and -1207 and TNFRII at positions -1709 and -3609 in patients with rheumatoid arthritis and in population control group. It was shown that the resulting frequency distribution of alleles and genotypes of TNFRI gene promoter in a group of population control is characteristic for Asian populations, for TNFRII gene polymorphisms and the frequency distribution differed from the European and Asian populations. Comparative analysis of allele and genotype frequencies of TNFRI gene promoter at positions -609 and -1207 and TNFRII and -3609 and positions -1709 in patients with rheumatoid arthritis and in population control group showed no statistically significant differences. However in the analysis of combinations has been shown that in patients with rheumatoid arthritis compared with the control population was significantly less common combination of genotypes TNFRI-609GT + TNFRII-3609CC.